PENTINGNYA PEMBERIAN ASI EKSKLUSIF PADA BAYI DI POSYANDU BUNGA TANJUNG DESA TANAH MERAH - Eliya Mursyida; Ratih Ayuningtiyas; Nurmaliza Hasan (Jurnal Pengabdian Masyarakat Multidisiplin, 2018)
Mother’s Milk (ASI) is a natural food that has nutritional value that is ideal with a balanced composition and in accordance with the needs for growth or development of the baby. Exclusive breastfeeding according to the World Health Organization (WHO) and the United Nations Children’s Fund (UNICEF) is breast milk given to infants aged 0-6 months without additional fluids or other foods. ASI provides many benefits for babies and mothers. For babies, one of them can prevent babies from various diseases, while for mothers can prevent breast cancer. The purpose of this service is to provide information or knowledge to the public about the importance of exclusive breastfeeding for babies in Posyandu Bunga Tanjung. Community service activities are carried out at Posyandu Bunga Tanjung using oral methods or presentations to the community. A total of 20 respondents (100%), obtained 90% of respondents who have good category knowledge. The dissemination of Exclusive Breastfeeding is a form of providing information to very mother who has a baby or prospective mother.